The contribution of inner and outer retinal photoreceptors to infra‐slow oscillations in the rat olivary pretectal nucleus. (3rd March 2016) - Orlowska‐Feuer, Patrycja; Allen, Annette E.; Storchi, Riccardo; Szkudlarek, Hanna J.; Lewandowski, Marian H.
Abstract: A subpopulation of olivary pretectal nucleus (OPN) neurons discharges action potentials in an oscillatory manner, with a period of approximately two minutes. This 'infra‐slow' oscillatory activity depends on synaptic excitation originating in the retina. Signals from rod‐cone photoreceptors reach the OPN via the axons of either classic retinal ganglion cells or intrinsically photosensitive retinal ganglion cells (ipRGCs), which use melanopsin for photon capturing. Although both cell types convey light information, their physiological functions differ considerably. The aim of the present study was to disentangle how rod‐cone and melanopsin photoresponses contribute to generation of oscillatory activity. Pharmacological manipulations of specific phototransduction cascades were used whilst recording extracellular single‐unit activity in the OPN of anaesthetized rats. The results show that under photopic conditions (bright light), ipRGCs play a major role in driving infra‐slow oscillations, as blocking melanopsin phototransmission abolishes or transiently disturbs oscillatory firing of the OPN neurons. On the other hand, blocking rod‐cone phototransmission does not change firing patterns in photopic conditions. However, under mesopic conditions (moderate light), when melanopsin phototransmission is absent, blocking rod‐cone signalling causes disturbances or even the disappearance of oscillations implying that classic photoreceptors are of greater importance under moderate light. Evidence is provided that all photoreceptors are required for the generation of oscillations in the OPN, although their roles in driving the rhythm are determined by the lighting conditions, consistent with their relative sensitivities. The results further suggest that maintained retinal activity is crucial to observe infra‐slow oscillatory activity in the OPN. Abstract : A subpopulation of olivary pretectal nucleus (OPN) neurons discharges action potentials in an oscillatory manner, with a period of approximately two minutes. This 'infra‐slow' oscillatory activity depends on synaptic excitation originating in the retina. The aim of the present study was to disentangle how rod‐cone and melanopsin photoresponses contribute to generation of oscillatory activity. Our results show that under photopic conditions (bright light) ipRGCs play a major role in driving infra‐slow oscillations, since blocking melanopsin phototransmission abolishes or transiently disturbs oscillatory firing of the OPN neurons. Under mesopic conditions (moderate light), when melanopsin phototransmission is absent, blocking rod‐cone signalling causes disturbances or even the disappearance of oscillations implying that classic photoreceptors are of greater importance under moderate light. We provide evidence that all photoreceptors are required for the generation of oscillations in the OPN, although their roles in driving the rhythm are determined by the lighting conditions.